1990
DOI: 10.1007/bf01322614
|View full text |Cite
|
Sign up to set email alerts
|

Gravity-dependent polarity of cytoplasmic streaming inNitellopsis

Abstract: The internodal cells of the characean alga Nitellopsis obtusa were chosen to investigate the effect of gravity on cytoplasmic streaming. Horizontal cells exhibit streaming with equal velocities in both directions, whereas in vertically oriented cells, the downward-streaming cytoplasm flows ca. 10% faster than the upward-streaming cytoplasm. These results are independent of the orientation of the morphological top and bottom of the cell. We define the ratio of the velocity of the downward- to the upward-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 45 publications
1
47
0
Order By: Relevance
“…While gravity could be sensed and curvature initiated by the individual plant cell (if it is capable of growth), the noise which accompanies all channel behaviour would likely ensure that gravity perception would be weak and stochastic and the response slow and variable. Wayne et al (1990) suggest that the primary reason the higher-plant graviperceptive ceils have starch-filled amyloplasts is simply to increase the density of the protoplast, i.e. to act like ballast, thus greatly refining the accuracy of graviperception.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While gravity could be sensed and curvature initiated by the individual plant cell (if it is capable of growth), the noise which accompanies all channel behaviour would likely ensure that gravity perception would be weak and stochastic and the response slow and variable. Wayne et al (1990) suggest that the primary reason the higher-plant graviperceptive ceils have starch-filled amyloplasts is simply to increase the density of the protoplast, i.e. to act like ballast, thus greatly refining the accuracy of graviperception.…”
Section: Discussionmentioning
confidence: 98%
“…Thus many (if not all) cells of the seedling are able to increase CaM mRNA levels in response to a gravitational stimulus and are thus gravisensitive, not just those containing amyloplasts. Wayne et al (1990) have recently suggested that graviperception in giant algal cells could be mediated by compression of the basal plasma membrane as a result of the weight of the cytoplasm. They show there is sufficient potential energy in this mechanism to open numerous stretch-activated calcium channels.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the biophysical parameters required to accurately model the statolith dynamics have been determined to varying degrees of accuracy, such as amyloplast density (Leach and Schoch, 1961;Robinson, 1985;Wayne et al, 1990) and maize and whiteclover statolith dimensions (Moore, 1986;Smith, 1996;Smith et al, 1997). If cytoplasmic viscosity is assumed to be 5 to 20 cP (Sack et al, 1985), the elastic forces due to interaction with the cytoskeletal network (F actin ) remain to be characterized.…”
Section: Physical Simulation Of the Tethered Statolith Model Of Gravimentioning
confidence: 99%
“…Thus, it has to be concluded that amyloplast sedimentation is not the sole mechanism in graviperception. At least, there exist two hypotheses about the mass responsible for gravisensing: the model of Wayne et al [26] postulating that the entire mass of a specialized cell is able to provide a signal for compression or tension (Fig. 19.6, left).…”
Section: The Plastid-based Gravisensingmentioning
confidence: 98%